Issues of appointing and conducting forensic examinations in criminal proceedings in some CIS countries (Czech Journal of Multidisciplinary Innovations, 2023)
The development of modern ideas about forensic expertise in domestic criminal justice and some CIS countries is being studied. In the article, taking into considerationthe comparative legal analysis of the legislation of some CIS countries regulation of forensic examination, the features of the national approaches to this activity are revealed.